“Estrategias de contenido y su efecto en la agencia de publicidad Emunatec” - Puchaicela Sánchez, Alexis Michael (2024)
The research aimed to examine the relationship between the content strategies applied by the advertising agency EMUNATEC in lead generation. The study addressed the interaction of these strategies to identify tactics that generated greater participation and response from these potential clients. To carry out the study, a quantitative approach was adopted, using a combination of literature review and field analysis at the EMUNATEC agency and the Social Scan platform. Data collection included information on advertising strategies, objectives, and examples of previous publications to evaluate the impact of content strategies on lead generation. The results highlighted that certain digital content strategies implemented by EMUNATEC generated more pronounced participation and response from leads, while specific areas were identified that could benefit from adjustments or alternative approaches. These findings also revealed areas of opportunity that influenced the positioning and competitive strategy of the agency in the advertising market. The study provided valuable insights, presenting a solid theoretical framework that supported the research in the context of EMUNATEC, as well as significant perspectives on its position and comparative strategy with similar agencies. In conclusion, the critical importance of content in positively influencing and effectively interacting with leads was emphasized, pointing out areas for improvement and potential for EMUNATEC. This analysis contributed to understanding the effectiveness of content strategies in lead generation and offered specific recommendations to optimize these strategies within the scope of the advertising agency.